Machinery investment decision and off-farm employment in rural China - Yueqing Ji; Funing Zhong; Xiaohua Yu (Leibniz Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2011)
This paper investigates the linkages between farmers' machinery investment decision and off-farm employment in China. Both the theoretical model and the empirical results based on a survey of 453 households in Anhui Province indicate that agricultural labor input and small-size machinery investment are gross complements rahter tha substitutes when machinery service is available in the market. Consequently, farmers with small machinery are more likely to reduce their off-time employment time.
Keywords: Q12; 330; Small-size Machinery; Off-Farm employment; Complements; China